Bolečina v stopalih pri bolnikih s sladkorno boleznijo tipa 2 - Novak, Primož (Medicinski razgledi, 2003)
Assessment of pain, disability, and activity limitation was made with the Foot Function Index in healthy volunteers, diabetic patients without symptomatic neuropathy and diabetic patients with symptomatic neuropathy. The Foot Function Index demonstrated a high level of internal consistency both for the total index and for the three subscales. Significant differences were found between the healthy volunteers, diabetic patients without symptomatic neuropathy and diabetic patients with symptomatic neuropathy for the total index and the three subscales. The Foot Function Index proved useful for the assessment of foot pain and consequent disability in patients with symptomatic diabetic neuropathy. It is less appropriate for the assessment of activity limitation in these patients.
Keywords: sladkorna bolezen; diabetična nevropatija; bolečina; stopalo